Electricity Supply Strategy for PT Freeport Indonesia’s Production Expansion - Hartanto, Ardi; Syarief, Rizal; Indrawan, Dikky (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
PT Freeport Indonesia (PTFI) plans to build a new power generation facility in the face of production expansion, especially underground mine and mill optimization, which has an impact on increasing the demand for electricity up to 374.8 MW. The selection of the right type of power plant, will greatly determine the continuity of the electricity supply operation. There are many things to consider, making it difficult for companies to determine the type of new power plant. Therefore, this study aims to (1) determine the most important factors to consider in the construction of PTFI's new power plant; (2) provide recommendations for the choice of the best type of new power plant for PTFI. This study uses the method of literature review, expert interviews and questionnaires, which are processed using the Analytical Hierarchy Process (AHP) method. The results of the study indicate that conformity with the existing power generation facilities and support from government policies are the most important factors and sub-factors that must be considered by PTFI in the construction of new power plants in the Special Mining Business License (IUPK) area. The recommended type of new power plant is the Dual Fuel Power Plant (DFPP). Keywords: analytical hierarchy process, consideration factors, electricity supply strategy, power generation, production expansion